ANALISIS PENGARUH KUALITAS LAYANAN, PERSEPSI TERHADAP HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN JASA (Studi pada pengguna layanan pengiriman barang J&T Express) - Damayant, Akmila Farida; Indriani, Farida (Faculty of Economics and Business Diponegoro University, 2021)
ABSTRACT This study aims to analyze the effect of service quality, perception of price and brand image on service purchase decisions for users of J&T Express freight forwarding services. The population in this study are J&T Express service users who have used this service to send their goods to buy goods through e-commerce at least once. The number of samples used was 110 respondents who were selected using purposive sampling method through questionnaires distributed online. The data from this study were processed using SPSS version 22. The results of this study indicate that brand image and perception of price have a positive and significant influence on service purchasing decisions, while service quality does not significantly affect service purchasing decisions.